Cholecystoduodenal fistula: a rare cause of gastric outlet obstruction-case report and imaging findings - Khanduri, Sachin; Kanojia, Avani; Chugh, Aniket; Singh, Abhishek; Chatterjee, Upasana (International Journal of Research in Medical Sciences, 2025)
Cholecystoduodenal fistula (CDF) is a rare complication of chronic gallstone disease, characterized by an abnormal communication between the gallbladder and duodenum. It is often asymptomatic but may present with complications such as gastric outlet obstruction (GOO), gallstone ileus, or cholangitis. Due to its nonspecific clinical presentation, CDF is often diagnosed incidentally on imaging or during surgery. In rare cases, it can lead to GOO, usually due to chronic inflammation-induced duodenal stenosis. Early recognition is crucial to prevent complications and guide appropriate management. We present the case of a 66-year-old male with a history of gallstone disease who developed progressive nausea, vomiting, and weight loss over two months. Abdominal examination revealed mild epigastric tenderness. Routine blood investigations were unremarkable. Contrast-enhanced CT abdomen showed pneumobilia, a contracted gallbladder with a direct fistulous communication to the duodenum, and significant enhancing thickening of the pyloroduodenal region, suggesting chronic inflammation-induced GOO. Upper gastrointestinal endoscopy confirmed pyloric stenosis without an obstructing gallstone. The patient underwent laparoscopic cholecystectomy with fistula closure and gastrojejunostomy, with significant symptomatic improvement postoperatively. This case highlights the suspicion of CDF in cases of unexplained GOO with pneumobilia.